Developing LSB method using mask in colored images - Karabatak, Murat; Yigit, Yildiray (Institute of Electrical and Electronics Engineers Inc., 2018)
The steganography word is derived from the combination of the steganos ('Greek passage'), which means 'covered, hidden or protected', and the graphein ('Greek passage'), which means 'writing'. The main purpose of steganography studies is to prevent the hidden data from being to obtained by unauthorized persons. In order to realize the basic purpose of the steganography methods, there should be minimal change in the pattern file. In this study, LSB method which is one of the methods of concealing digital image information is examined. In this study, a new method of data hiding is proposed in order to minimize the changes occurring in the cover file while hiding the data with LSB method and to create the most appropriate mask to make it difficult to obtain hidden data. © 2018 IEEE.
6th International Symposium on Digital Forensic and Security, ISDFS 2018 -- 22 March 2018 through 25 March 2018 -- Antalya -- 136277
Keywords: Finding Optimum Mask; Image; LSB; Sound; Steganography; Video